2002
DOI: 10.1006/mthe.2002.0630
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Toxicity Studies of VSVG-Pseudotyped Lentiviral Vector after Intravenous Administration in Mice with the Observation of in Vivo Transduction of Bone Marrow

Abstract: Lentiviral vectors can confer high levels of gene transfer and transgene expression in a variety of cell types. However, the biodistribution and toxicity after intravenous administration have not been reported. To address these issues of biodistribution and toxicity, an HIV-1-based vector, HR'cmvGFP, was administered to normal BALB/c mice by tail-vein injection. Nine different organs and bone marrow were evaluated by real-time quantitative PCR (QPCR) assay capable of a broad range of quantitation (5-log fold) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 45 publications
12
77
1
Order By: Relevance
“…Similar results have also been reported by others. 27 Figure 4 Tissue sections of DTA vector-treated and untreated mice. Tail vein injection delivered approximately 0.2 ml of the DTA lentiviral vector with a 3.5 mg p24/ml p24 count.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have also been reported by others. 27 Figure 4 Tissue sections of DTA vector-treated and untreated mice. Tail vein injection delivered approximately 0.2 ml of the DTA lentiviral vector with a 3.5 mg p24/ml p24 count.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in agreement with an earlier study where VSV-G-pseudotyped HIV vectors were found to mainly target the spleen, liver and bone marrow of mice injected i.v. 33,34 Discussion Previous evaluation of HIV-1 lentivectors following systemic delivery have demonstrated long-term expression of the transgene for up to 1 year, depending on the transgene and host. [33][34][35] An alternative to HIV-1 is the EIAV-based vector, which has been developed, in part, because HIV-1 is a human pathogen and as a result may face extra hurdles in clinical use.…”
Section: Eiav Vector For Systemic Delivery Of Proteinsmentioning
confidence: 95%
“…33,34 Discussion Previous evaluation of HIV-1 lentivectors following systemic delivery have demonstrated long-term expression of the transgene for up to 1 year, depending on the transgene and host. [33][34][35] An alternative to HIV-1 is the EIAV-based vector, which has been developed, in part, because HIV-1 is a human pathogen and as a result may face extra hurdles in clinical use. In addition to this, the potential advantages of EIAV are its relative simplicity compared to HIV-1, the inability of the parent virus to replicate in human cells and the nonlethal nature of the infection in its natural host, the genus Equidiae.…”
Section: Eiav Vector For Systemic Delivery Of Proteinsmentioning
confidence: 95%
“…Other techniques include nonquantitative or semiquantitative PCR, FISH (approx. 50%), Southern blot 1,2 and reporter gene expression (LacZ, [1][2][3][4][5][6]7 luciferase, [8][9][10][11] and GFP 12 ).…”
Section: Technique Validationmentioning
confidence: 99%
“…Some authors also used an internal control, which is often a competitive piece of DNA used in the same reaction tube. 12,15,[17][18][19][20] The advantage of this technique is a precise control of inhibition in the same tube, the inconvenience being the sensitivity decrease because of competition. We would recommend qPCR in triplicate, with spiking of one of the reaction tubes with a low DNA amount (as in Hanke et al 13 ).…”
Section: Technique Validationmentioning
confidence: 99%